The Effectiveness of Chlorhexidine and Air Polishing System in the Treatment of Candida albicans Infected Dental Implants: An Experimental In Vitro Study - Pier Carmine Passarelli; Marta De Leonardis; Giovan Battista Piccirillo; Viviana Desantis; Raffaele Papa; Edoardo Rella; Giuseppe Niccolò Mastandrea Bonaviri; Piero Papi; Giorgio Pompa; Guido Pasquantonio; Paolo Francesco Manicone; Antonio D'Addona (MDPI AG, 2020)
Background: Peri-implantitis is an inflammatory disease with an increasing diffusion rate which can affect the long-term survival of a prosthetic rehabilitation. The present study focused on the decontaminating efficacy of chlorhexidine and air polishing system with sodium bicarbonate powder against Candida albicans, a microorganism which seems to have a superinfecting opportunistic role in the pathology. The aim of the authors was to investigate and compare the effectiveness of these treatments, commonly used in clinical practice. Methods: An in vitro study was conducted to analyze the effects of two widely used therapeutic aids for the disinfection of affected titanium implants: chlorhexidine (CHX) and air polishing with sodium bicarbonate powder (P). A qualitative and quantitative comparative analysis of the residual biofilm was carried out using a colorimetric assay (XTT) and scanning electron microscopy (SEM) observation. The experiment was conducted both on machined titanium surfaces and on rough sandblasted ones with the aim of bringing out differences in the therapeutic outcomes concerning the superficial texture of the implant. The null hypothesis was that no difference could be detected between the samples, regarding both the treatments performed and the nano-structural features of titanium. Results: The best results (on both types of implant surfaces) were obtained when combining the use of chlorhexidine and air polishing (C + P). A linear decrease in the optical density (OD) values recorded at three different time points (30 s, 1 min, 5 min) was also observed passing from the first to the last one. When observed under scanning electron microscope rough surfaces showed an extensive and highly structured biofilm, more complex if compared to the one encountered when analyzing machined implants. Conclusions: the present pilot study showed that rough surfaces can promote fungal adhesion and eventually hinder the outcome of a decontaminating treatment. For this purpose, the physio-chemical technique is always more efficient if compared to a single-technique approach regardless of the surface characteristics.